Cyanoboletus abieticola (Boletaceae, Basidiomycota), a new species from Mexico - Jesús García-Jiménez; Olivia Ayala-Vásquez; Javier Isaac de la Fuente; Roberto Garibay-Orijel; Fortunato Garza-Ocañas; Edgardo Ulises Esquivel-Naranjo; Felipe Manuel Ferrusca-Rico; Fidel Landeros Jaime (Revista Mexicana de Biodiversidad)
Cyanoboletus abieticola is described as a new species to science. This species is characterized by the viscid pileus, cylindric to bacilliform basidiospores ([14.1] 16.2 ± 1.1 [17.5] × [5] 5.5 ± 0.3 [5.9] μm, Q [2.8] 3.0 ± 0.1 [3.2]), and its gregarious habit in mixed coniferous forests dominated by Abies religiosa or A. guatemalensis. Photographs, drawings, and the phylogenetic analysis of 3 genetic data sets (ITS, nucLSU, and RPB2) of the new species are presented.